Bibliometric analysis of kinship analysis from 1960 to 2023: global trends and development - Liu, Yanchen; Sun, Chaoran; Si, Haoyuan; Peng, Zixuan; Gu, Liya; Guo, Xiangnan; Song, Feng (Frontiers in Genetics, 2024)
Kinship analysis is a crucial aspect of forensic genetics. This study analyzed 1222 publications on kinship analysis from 1960 to 2023 using bibliometric analysis techniques, investigating the annual publication and citation patterns, most productive countries, organizations, authors and journals, most cited documents and co-occurrence of keywords. The initial publication in this field occurred in 1960. Since 2007, there has been a significant increase in publications, with over 30 published annually except for 2010. China had the most publications (n=213, 17.43%), followed by the United States (n=175, 14.32%) and Germany (n=89, 7.28%). The United States also had the highest citation count. Sichuan University in China has the largest number of published articles. The University of Leipzig and the University of Cologne in Germany exhibit the highest total citation count and average citation, respectively. Budowle B was the most prolific author and Kayser M was the most cited author. In terms of publications, Forensic Science International-Genetics, Forensic Science International, and International Journal of Legal Medicine were the most prolific journals. Among them, Forensic Science International-Genetics boasted the highest h-index, citation count, and average citation rate. The most frequently cited publication was “Van Oven M, 2009, Hum Mutat”, with a total of 1,361 citations. The most frequent co-occurrence keyword included “DNA”, “Loci”, “Paternity testing”, “Population”, “Markers”, and “Identification”, with recent interest focusing on “Kinship analysis”, “SNP” and “Inference”. The current research is centered around microhaplotypes, forensic genetic genealogy, and massively parallel sequencing. The field advanced with new DNA analysis methods, tools, and genetic markers. Collaborative research among nations, organizations, and authors benefits idea exchange, problem-solving efficiency, and high-quality results.